2017
DOI: 10.1080/21541264.2017.1321612
|View full text |Cite
|
Sign up to set email alerts
|

Ras and Rho GTPase regulation of Pol II transcription: A shortcut model revisited

Abstract: Transcriptional control is critical in relaying signals mediated by Ras and Rho family small GTPases to effect gene expression. In the classical model, signaling components such as MAP kinase target sequence-specific transcription factors, which in turn recruit RNA polymerase (Pol) II holoenzyme to the promoter and activate transcription. Findings in recent years have led to the proposal of a shortcut model in which the Mediator components of the Pol II holoenzyme are regulated by signaling pathways. A very re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The transcriptional procedure is mediated by Ras and Rho family small GTPases to alter gene expression. It has been well documented that an evolutionarily conserved Rho GTPase signaling pathway that targets proteasomes as CTD phosphatases can directly modify the RNA Pol II CTD [ 27 , 28 ]. Indeed, a previous study reported that Rho family GTPases, such as CDC42, can alter the phosphorylation of Ser2 and Ser5 in the CTD of RPB1, the largest subunit of Pol II, thereby affecting gene expression and influencing the size, shape, and number of cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional procedure is mediated by Ras and Rho family small GTPases to alter gene expression. It has been well documented that an evolutionarily conserved Rho GTPase signaling pathway that targets proteasomes as CTD phosphatases can directly modify the RNA Pol II CTD [ 27 , 28 ]. Indeed, a previous study reported that Rho family GTPases, such as CDC42, can alter the phosphorylation of Ser2 and Ser5 in the CTD of RPB1, the largest subunit of Pol II, thereby affecting gene expression and influencing the size, shape, and number of cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…How these kinases and phosphatases are controlled by upstream signals in gene expression regulation have received increasing attention. Accumulating evidence suggests the existence of two models of transcriptional control ( Figure 4 ) [ 54 ]. In the “ classical ” model of transcriptional control, which is frequently described in molecular genetics or cell biology textbooks, extracellular proliferation cues first activate intracellular signaling switches, such as the well-studied Ras and Rho families of small GTPases, which in turn activate the MAP kinase cascade.…”
Section: Functional Conservation Of Cdk and Ctd Phosphatasesmentioning
confidence: 99%
“…In the “ classical ” model of transcriptional control, which is frequently described in molecular genetics or cell biology textbooks, extracellular proliferation cues first activate intracellular signaling switches, such as the well-studied Ras and Rho families of small GTPases, which in turn activate the MAP kinase cascade. Subsequently, phosphorylated MAPKs phosphorylate various sequence-specific transcription factors, which then become active and bind to the gene-specific enhancer and consequently, recruit Pol II, by interacting with the general transcription factor TFIIH complex, to the core promoter of those genes to be transcribed [ 54 ]. Moreover, this interaction stimulates Ser5P in the CTD of RPB1 via activation of CDK7 present in the general transcription factor TFIIH complex and/or the mediator complex [ 55 , 56 , 57 ].…”
Section: Functional Conservation Of Cdk and Ctd Phosphatasesmentioning
confidence: 99%
“…Ras superfamily small GTPases, including Ras and Rho families, act as key signaling switches in regulating gene expression, and consequently deregulation of these signaling GTPases is frequently associated with many diseases including cancer [1][2][3][4][5]. There are two models regarding Ras and Rho GTPase control of RNA polymerase (Pol) II transcription: the well-known classical or "indirect" model, and the recently re-emerged direct or "shortcut" model [6]. The classical model has been described in genetics and cell biology textbooks and literature and presented as a paradigm in oncogenic signaling networks.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the shortcut model allows activated GTPases to target protein kinase A or proteasome to regulate a component of Mediator [7] or Pol II [8]. Given that the shortcut model does not involve the MAP kinase cascade and instead directly regulates Pol II or its components, this model has a potential of efficiently regulating transcription so as to rapidly bring about the broad changes in gene expression in response to dynamic intracellular and extracellular changes [6][7][8].…”
Section: Introductionmentioning
confidence: 99%